(untitled) (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Formulation and evaluation of floating tablets of ciprofloxacin hydrochloride. Materials and Methods: In the present study the formulations were prepared by wet granulation technique using different proportions of hydroxypropyl methylcellulose (HPMC) K100M, HPMC K15M and Carbopol 934 as Swellable polymers. Citric acid has stabilizing effect and sodium bicarbonate is used as buoyancy-imparting agent. Results and Discussion: The prepared formulations were evaluated for different parameters during its pre-compression and Post-compression stages. The release characteristics of the formulations were studied in in-vitro conditions. The in-vitro dissolution study of formulation F4 was 99.12% within 12 h for good release and was fitted to kinetics of drug release for R2 value of korsmeyer-peppas model is 0.9854. The drug release was diffusion mediated and from the peppa’s plot, it is confirmed that it is of non-fickian type. Conclusion: As an extension of this work for formulation F4, bioavailability, pharmacokinetic, and in vivo studies can be done in future to develop as suitable candidate for a novel drug delivery system.